The Effect of Economic Variables on CO2 Emissions in 7 Asian Countries (Efficient: Indonesian Journal of Development Economics, 2023)
This study aims to determine and analyze the direct and indirect effects of economic variables on carbon dioxide (CO2) emissions in 7 Asian countries during the 2010-2019 period. This research uses a descriptive quantitative approach and path analysis model. The results show that employment in the industry directly has an influence on CO2 emissions, the population has an influence on CO2 emissions, energy consumption has an influence on CO2 emissions, and FDI has an influence on CO2 emissions. Whilindirectly employment in the industry has no effect on CO2 emissions through economic growth, the population has no influence on CO2 emissions through economic growth, energy consumption has no effect on CO2 emissions through economic growth, and FDI has an influence on CO2 emissions through economic growth.